Cilnidipine for Amlodipine Induced Pedal Edema and its Anti-hypertensive Effect in a Tertiary Care Teaching Hospital of Western Nepal - Kafle, Ram Chandra; Sapkota, Subash; Maskey, Abhisek (Journal of Nepal Health Research Council, 2021)
Background: Hypertension is the most common cardiovascular disease. In Nepal, 27.3% populations are suffering from hypertension. Amlodipine is the most frequently prescribed anti-hypertensive drug. Up to 15% of patients develop pedal edema with amlodipine that may lead to discontinuation. Cilnidipine, a new calcium channel blocker, found equally effective and edema is uncommon in different studies from India. We aimed to study anti-hypertensive effect and to assess resolution of amlodipine induced Pedal edema with clinidipine. Methods: This was a prospective, single centre observational study. Study was conducted in the department of cardiology, Manipal teaching hospital from 7th May to 6th November 2020. Hypertensive Patients who were on amlodipine for at least 6 months and presented with pedal edema were enrolled for the study. Results: Total of 107 patients were enrolled for the study. The mean age of patients was 56.35 ± 12.84 years, ranged from 29 to 85 years and more than half(52.3 %) were male. Of the 107 patients, 90 (84.1%) patients received 10mg of clinidipine. On follow up, all patients except three (2.8%) had resolution of pedal edema. The blood pressure reduction with clinidipine was comparable with amlodipine (p: >0.05). Three patients who had persistent edema on follow up were on higher dose of clinidipine. Conclusions: The newer L and N type CCB, Clinidipine has comparable efficacy with amlodipine and well tolerated in our population. Though the incidence of pedal edema is low but can occur with clinidipine especially with higher doses. Keywords: Amlodipine; ankle edema; clinidipine; hypertension